The control of an upper limb exoskeleton system for passive stroke rehabilitation: An active force control approach - Anwar, P. P. Abdul Majeed; Zahari, Taha; M. A., Abdullah; I.M., Khairuddin; M. A., Zakaria (Centre for Advanced Research on Energy, 2018)
This paper examines the efficacy of a robust class control scheme namely active force control (AFC) on a two degrees of freedom upper limb exoskeleton system in performing typical rehabilitation trajectory on the shoulder and elbow joints. The dynamics of the system was attained via the Lagrangian principle. The ability of the Proportional-Derivative AFC (PDAFC) architecture optimized by means of fuzzy logic (FL) and artificial neural network (ANN) against classical PD in mitigating constant disturbance effect on the aforesaid joints were also evaluated. It was demonstrated from the simulation investigation that the PDANNAFC scheme triumphs against other schemes evaluated.